Lewis And Clark : Step Into Reading 3 - Shirley Raye Redmond (New York, United States Golden Books Publishing Company, Inc., 2003)
In 1803, President Thomas Jefferson sends Lewis and Clark out west to explore. He tells them to make maps. He tells them to draw pictures and collect plants. Most importantly, he tells them to send presents! What kind of present is good enough for a president? Beginning readers will truly enjoy reading about this fun and little-known slice of American history.
Keywords: Read Aloud Non Fiction